What are the best societal investments for improving people's health?. (30th August 2018) - Webber, Laura; Chalkidou, Kalipso; Morrow, Susie; Ferguson, Brian; McPherson, Klim
Abstract : Healthcare alone cannot improve population health. Laura Webber and colleagues advocate a "health in all policies" approach, with protected funding for preventive interventions